Dynamic Covalent Michael Acceptors to Penetrate Cells: Thiol‐Mediated Uptake with Tetrel‐Centered Exchange Cascades, Assisted by Halogen‐Bonding Switches. (17th November 2022) - Shybeka, Inga; Maynard, John R. J.; Saidjalolov, Saidbakhrom; Moreau, Dimitri; Sakai, Naomi; Matile, Stefan
Abstract: Chalcogen‐centered cascade exchange chemistry is increasingly understood to account for thiol‐mediated uptake, that is, the ability of reversibly thiol‐reactive agents to penetrate cells. Here, reversible Michael acceptors are shown to enable and inhibit thiol‐mediated uptake, including the cytosolic delivery of proteins. Dynamic cyano‐cinnamate dimers rival the best chalcogen‐centered inhibitors. Patterns generated in inhibition heatmaps reveal contributions from halogen‐bonding switches that occur independent from the thyroid transporter MCT8. The uniqueness of these patterns supports that the entry of tetrel‐centered exchangers into cells differs from chalcogen‐centered systems. These results expand the chemical space of thiol‐mediated uptake and support the existence of a universal exchange network to bring matter into cells, abiding to be decoded for drug delivery and drug discovery in the broadest sense. Abstract : Introduced as the first explicitly tetrel‐centered cascade exchangers, Michael acceptors are shown to enable and inhibit thiol‐mediated uptake, generate distinct patterns in heatmaps to decode uptake circuitry, integrate novel halogen‐bonding switches, deliver proteins to the cytosol, and break, as dimers, records for uptake inhibition related to drug discovery.